Riberalta: extractivistas bajo una élite tradicional - Kaimowitz, D.; Bojanic Helbingen, A.J. (1998)
This chapter looks at the municipal government of Riberalta, Bolivia and its role in forest management. Riberalta is located in the northern Bolivian Amazon and depends heavily on Brazil nuts harvesting and processing, as well as logging and agriculture. The traditional local elite has maintained control over the municipal government. Since passage of the 1996 forestry law the municipal government has attempted to create a municipal forest reserve and a local protected area but has fought strongly against government titling of indigenous territories. (DK)